The effects of two different dosages of BCAA supplementation on a serum indicators of muscle damage in wrestlers - Amirsasan, R.; Nikookheslat, S.; Sari-Sarraf, V.; Kaveh, B.; Letafatkar, A. (International Journal of Wrestling Science, 2011)
Background and Aim: Few studies have been done to examine the effect of different dosages of branched-chain amino acid (BCAA) supplementation on muscle damage indices in wrestlers. The purpose of this research was to compare the effects of two dosages of BCAA on muscle damage indices after heavy resistance exercise in wrestlers. Methods: 29 young wrestlers were randomly selected and divided into three groups. All subjects participated in heavy weight resistance exercise (3 sets, 10 repetitions, 80% 1RM). The BCAA was given at doses of 210 and 450 mg/kg body weight for supplemental groups 1 and 2 respectively, 30 minutes before and after the exercise test and dextrin was given at a dose of 210 mg/kg body weight for the placebo group. To identify enzyme activity (IU/L), venous blood samples were obtained 30 min prior to exercise and at 24 and 48 hrs post exercise. Data were statistically analyzed using ANOVA with repeated measures and the Bonfferoni test (P=0.05). Results: Based on this study results, creatine kinase (CK), lactate dehydrogenase (LDH), creatine kinase isoenzyme MB (CKMB) activity were significantly increased (p<0.05( in all groups. CK, LDH, CKMB indices having the highest activity in the placebo group, but there were no significant differences between all groups. Conclusion: These results provide evidence that the use of two different dosages of BCAA did not decrease the muscle damage associated with heavy resistance exercise.